Determinación de la cadena de comercialización de tres variedades de papa (Solanum Tuberosum) en la parroquia de Machachi, cantón Mejía provincia de Pichincha. - Manya Cislema, Jefferson Nestor (2023)
This research study was carried out in Pichincha Province, Mejía Canton, in Machachi Parish at Latitude: 0°30.6066’S and Longitude: 78°34.0272’W. The objective of this study was to locate the marketing chain of 3 varieties of potato (Solanum tuberosum) and establish price fluctuation in the different links of the marketing chain. In the first phase, a visit was made to the study area, a total of 384 surveys were applied with required questions such as the cost of potato production per hectare, marketing price in quintals, marketing site, among others. The information obtained stated that the marketing chain of Machachi Parish, Mejía Canton, Pichincha Province is composed of producer-intermediary (Wholesaler-Retailer) and final consumer, where producers belong to the parishes Alóag, Chaupi, Machachi, Uyumbicho, Tambillo, Aloasí, Cutuglahua in Mejía Canton and market their products in the Machachi market (‘Centro de Comercialización de Productores del Cantón Mejía’), the wholesale intermediary buys in the Machachi market and sells in ‘La Argelia’ Parish (‘Mercado Mayorista de Quito’) in Quito Canton, the retail intermediary buys in the wholesale market of Quito or in the market of Machachi (‘Centro de Comercialización de Productores del Cantón Mejía’) and sells in the parishes Guamaní, Chillogallo, Magdalena, Ecuatoriana, Quitumbe, San Bartolo, Solanda. Price fluctuation in the different marketing links is established by factors such as; quality, sales volume, competition (supply and demand), variety and investment.